A systematic review on industrial 4.0 readiness for environmental sustainability considering cultural influences - Ghazali, Ihwan; Semiun, Nasri; Mohamad, Effendi; Tanjung, Tia (The Indonesian Institute of Science and Technology Research, 2025)
This systematic literature review (SLR) investigates the development of sustainability guidelines tailored for Industry 4.0, emphasizing the influence of cultural factors and the multidimensionality of existing sustainability models. Industry 4.0 represents a pivotal shift in industrial operations, integrating advanced technological innovation with a human-centric focus to achieve sustainability goals. Cultural factors, however, play a crucial role in shaping the success of such initiatives. This research examines how the various dimensions of sustainability models are influenced by cultural considerations and provides a comprehensive analysis of their impact on Industry 4.0 readiness. The findings of the SLR underscore that aligning technology with local cultural values, engaging stakeholders across diverse societal levels, and fostering capacity-building through culturally relevant training and education are vital to enhancing the effectiveness of sustainability practices. The proposed guidelines advocate for incorporating cultural analysis during the early planning phases, developing culturally sensitive communication strategies, formulating adaptable and flexible policies, and promoting international collaboration that respects cultural diversity. This study contributes valuable insights into the dynamic interplay between cultural influences and sustainability within the Industry 4.0 framework, emphasizing the importance of culturally responsive strategies for achieving enduring sustainable outcomes.